Patient Experience in the Digital Era: A Scoping Review of eWOM and Service Quality in Hospital Outpatient Care - Fandhira, Novalia Larissa; Farida, Naili; Arso, Septo Pawelas (GoAcademica Research & Publishing, 2025)
Healthcare experiences have been transformed in the digital age by patients' communication. Electronic word of mouth (eWOM) is no longer simply a technical phenomenon. It plays an essential role in influencing the way that service quality and satisfaction are perceived in hospital outpatient care. Online feedback from patients can describe their positive and negative experiences, making eWOM a key means of gauging what matters most to them. In this scoping review, we investigate the ways in which eWOM reflects and influences service quality and patient experience in outpatient care. The goal was so hospitals could actually develop and implement solutions that are responsive to patient needs and sincere. The infusion of such digital insight can drive patient satisfaction and increase the hospital's reputation in the community. Following the PRISMA-ScR framework, a literature search was performed in the Scopus database (2013–2025) employing PCC-based keywords: electronic word of mouth, online review, hospital, and outpatient. Of 527 records, 14 studies fulfilled the inclusion criteria. A narrative synthesis of the data, including variables of eWOM, quality dimensions of service provision, and patient outcomes. Findings suggest eWOM has a notable impact on decision and hospital reputation. Negative reviews (particularly about waits, communication and staff attitude) weighed a bit heavier than positive ones. Responsiveness, assurance, empathy, and reliability stood out as the most relevant dimensions of service quality aligned to SERVQUAL. Digital feedback rose during the COVID-19 pandemic, with an increased emphasis on hygiene and safety. eWOM acts as an immediate feedback method of supplementing traditional quality assessments. Hospitals are encouraged to implement eWOM analysis techniques as part of their quality improvement systems in order to provide digitalized and patient-oriented care.